2013
DOI: 10.5897/ajb12.2433
|View full text |Cite
|
Sign up to set email alerts
|

Acute toxicity of the chloroacetanilide herbicide butachlor and its effects on the behavior of the freshwater fish Tilapia zillii

Abstract: Acute toxicity of butachlor, a chloroacetanilide herbicide (2-chloro-N-[2, 6-diethylphenyl] acetamide) to Tilapia zillii, was studied in a semi static bioassay. The 24, 48, 72 and 96 h LC 50 values (with 95% confidence limits) estimated by probit analysis were 3.13 (2.88 to 4.61), 1.93 (0.63 to 4.41), 1.27 (0.59 to 1.92) and 1.25 (0.60 to1.85) mgl-1 , respectively. There were significant differences (p<0.05) in the LC 50 values obtained at different exposure times and the safe levels estimated by different met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…For example, one study has shown that chloroacetanilide herbicides such as alachlor increase the likelihood of developing Parkinson's disease [25]. Ecotoxicological studies suggest that these herbicides are the causal agents for DNA damage and tumor induction in rats, fish, and human lymphocyte cells found in in vitro studies [26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…For example, one study has shown that chloroacetanilide herbicides such as alachlor increase the likelihood of developing Parkinson's disease [25]. Ecotoxicological studies suggest that these herbicides are the causal agents for DNA damage and tumor induction in rats, fish, and human lymphocyte cells found in in vitro studies [26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Annune et al [22] and Olusegun [23] reported similar findings. Nwani et al [24] also reported "skin discolouration in Tilapia zilli exposed to the chloroacetanilide herbicide butachlor". Ikele et al [25] similarly observed that the "C. gariepinus normal darkly pigmentation in the dorsal and lateral parts was changed to very light pigmentation when exposed to diethyl phthalate.…”
Section: Discussionmentioning
confidence: 99%